Dissecting the causal relationship between household income status and genetic susceptibility to cardiovascular-related diseases: Insights from bidirectional mendelian randomization study - Xifeng Zheng; Yu Yang; Jianying Chen; Bing Lu (BMC, 2023)
Abstract Objectives Observational studies have revealed that socioeconomic status is associated with cardiovascular health. However, the potential causal effect remains unclear. Hence, we aimed to investigate the causal relationship between household income status and genetic susceptibility to cardiovascular-related diseases using a bidirectional Mendelian randomization (MR) study. Methods An MR study based on a large-sample cohort of the European population from a publicly available genome-wide association study datasets was conducted using a random-effects inverse-variance weighting model as the main standard. Simultaneously, MR-Egger regression, weighted median, and maximum likelihood estimation were used as supplements. Sensitivity analysis, consisting of a heterogeneity test and horizontal pleiotropy test, was performed using Cochran's Q, MR-Egger intercept, and MR-PRESSO tests to ensure the reliability of the conclusion. Results The results suggested that higher household income tended to lower the risk of genetic susceptibility to myocardial infarction (OR: 0.503, 95% CI = 0.405-0.625, P < 0.001), hypertension (OR: 0.667, 95% CI = 0.522-0.851, P = 0.001), coronary artery disease (OR: 0.674, 95% CI = 0.509-0.893, P = 0.005), type 2 diabetes (OR: 0.642, 95% CI = 0.464-0.889, P = 0.007), heart failure (OR: 0.825, 95% CI = 0.709-0.960, P = 0.013), and ischemic stroke (OR: 0.801, 95% CI = 0.662-0.968, P = 0.022). In contrast, no association was evident with atrial fibrillation (OR: 0.970, 95% CI = 0.767-1.226, P = 0.798). The reverse MR study suggested a potentially negative trend between heart failure and household income status. A sensitivity analysis verified the reliability of the results. Conclusions The results revealed that the population with higher household income tended to have a lower risk of genetic susceptibility to myocardial infarction and hypertension.